Inclusão produtiva com segurança sanitária: uma avaliação da política de interesse sanitário destinada aos microempreendedores individuais de alimentos - Cruz, Samara de Mesquita Góes (2021)
According to Resolution-RDC ANVISA number 49/2013, aspects of productive inclusion for individual micro-entrepreneurs subject to the action of health surveillance were established, aiming to promote the income generation, employment, social inclusion and socioeconomic development in the country, taking advantage of the actions of the Health Surveillance to preserve the food’s quality and protect the population’s helath. Based on the methodology of In-Depth evaluation, this study aimed to evaluate how the health policy of individual microentrepreneurs is understood by their beneficiaries and what are their perceptions about the effectiveness of the Health Surveillance inspector’ performance, as well as what are its consequences in the economic and social development of these small businesses. The specific objectives are: to understand what motivated the individuals surveyed to undertake in the food market; to evaluate whether the rights listed in Resolution-RDC number 49/2013 are perceived by its beneficiaries; to analyze whether there are specific health actions in the municipality for the development of food micro-entrepreneurs; and, finally, to understand how the Health Surveillance inspector understands his social role as a promoter of micro entrepreneurs’ development. Data collection included a bibliographic research, documental data search, analysis of institutional documents and semi-structured interviews carried out with two categories of subjects: nine interviews with individual food microentrepreneurs and eleven interviews with inspectors from the food health surveillance field in Fortaleza City. The data analysis used as a method the content analysis of the speeches, starting from a pre-analysis, followed by the definition of categories of interest and ending with the interpretation of the results. The field research revealed that sanitary surveillance has a great influencing potential in the development of small businesses, but nowadays it is involved in a State market vision, with a focus on the quantitative instead of the qualitative. On the other hand, the productive inclusion of micro-entrepreneurs takes place in a precarious way, motivated by the need for survival, where the benefits of the policy are not perceived by its beneficiaries, with little State support for business development and without many possibilities for growth.